Learning Outcomes of the Inquiry-in-Action Model for Chemistry Experimentation (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2024)
There is overwhelming evidence supporting the decline of science education in Liberia. In an effort to contribute to the solution, we conducted a study to examine the impact of inquiry-based experimentation and conventional demonstration on the conceptual understanding of solutions and solubility among grade eleven students. We also investigated the relationship between students' achievement scores in solutions and solubility and their science inquiry process skills. A cluster random sample of eight schools was initially selected from 12 out of 31 high schools that had the necessary space and materials for experimentation. Using a Non-equivalent control group research design, the experimental group received instruction using inquiry-based experimentation, while the control group received instruction using traditional demonstration methods, for a period of six weeks. The results were analyzed using the Mann-Whitney U, and Wilcoxon Signed Rank tests. The findings indicated that inquiry-based experimentation reduced students' anxiety and increased their confidence in chemistry experiments. Although the inquiry-in-action model enhanced learners' conceptual understanding of solutions and solubility, it did not significantly improve their mastery of the mathematical components of the test. However, it did significantly enhance students' science inquiry process skills. It should be noted that while the inquiry-in-action model positively influenced learners' attitudes toward their preferences, behavior, and anxieties in chemistry experiments, it also led to a general demotivation to learn chemistry through experimentation. Additionally, there was a positive correlation between students' attitudes toward teaching and learning chemistry through experiments and their science inquiry process skills. However, this correlation was stronger between students' attitudes towards the demonstration of experiments and their science inquiry process skills compared to the attitudes towards the inquiry-in-action model and science inquiry process skills. This suggests that the traditional demonstration method is not entirely ineffective, and a combination of both demonstration and inquiry-based experimentation approaches may be a viable way to maximize the benefits of science experiments.